IFNγ-dependent, spontaneous development of colorectal carcinomas in SOCS1-deficient mice - Hanada, Toshikatsu (The Rockefeller University Press, 2006)
Approximately 20% of human cancers are estimated to develop from chronic inflammation. Recently, the NF-κB pathway was shown to play an essential role in promoting inflammation-associated cancer, but the role of the JAK/STAT pathway, another important signaling pathway of proinflammatory cytokines, remains to be investigated. Suppressor of cytokine signaling-1 (SOCS1) acts as an important physiological regulator of cytokine responses, and silencing of the SOCS1 gene by DNA methylation has been found in several human cancers. Here, we demonstrated that SOCS1-deficient mice (SOCS1(−/−)Tg mice), in which SOCS1 expression was restored in T and B cells on a SOCS1(−/−) background, spontaneously developed colorectal carcinomas carrying nuclear β-catenin accumulation and p53 mutations at 6 months of age. However, interferon (IFN)γ(−/−)SOCS1(−/−) mice and SOCS1(−/−)Tg mice treated with anti-IFNγ antibody did not develop such tumors. STAT3 and NF-κB activation was evident in SOCS1(−/−)Tg mice, but these were not sufficient for tumor development because these are also activated in IFNγ(−/−)SOCS1(−/−) mice. However, colons of SOCS1(−/−)Tg mice, but not IFNγ(−/−)SOCS1(−/−) mice, showed hyperactivation of STAT1, which resulted in the induction of carcinogenesis-related enzymes, cyclooxygenase-2 and inducible nitric oxide synthase. These data strongly suggest that SOCS1 is a unique antioncogene which prevents chronic inflammation-mediated carcinogenesis by regulation of the IFNγ/STAT1 pathways.